MR Role of Islamic Stock Market and Capital Formation Promoting Indonesia’s Economy - Rasyidin, M.; Sulong, Zunaidah; Afendi, Arif; Nova, Nova; Diah, Muhammad; Zulfikar, Zulfikar (Forum Kerjasama Pendidikan Tinggi, 2023)
Capital formation and Indonesia’s economy. The study employed ARDL bounds-testing for the long run relationship and ECM for the short run dynamics. The data used in this study were annual secondary data in the form of time series from 1995 to 2020. The data for the study were obtained from multiple sources such as World Bank database, Asian Development and publication from relevant plurals. To measure stock market development was proxied with stock value traded. The results of the data analyzed showed that there might with no a short run significant relationship between islamic capital market, capital formation and Indonesia’s economy. In the long run VECM shows that capital formation has a significant positive association with Indonesia’s economy and a negative and non-significant relationship between islamic stock market and Indonesia’s economy. Investors and policymakers should take into account the information and fluctuations the future movements of Islamic stock price. The companies and the government has a strong commitment to increase investment promotion, facilitate and development, the create a conducive investment climate to encourage increased Indonesia’s economy. Recovery of the Indonesian economy might put Islamic stock market at advantage because there is possibility that global investors will switch back their investment.. There is no literature review on Islamic stock market, capital formation and economic growth. Therefore, we are going to fill this gap to investigates the link between three variabel empirically using VAR model.